Novel Topical Intranasal Therapies in the Management of Allergic Rhinitis (Canadian Allergy & Immunology Today, 2021)
Allergic rhinitis (AR) is one the most common immunologic conditions affecting adults. Its prevalence has increased over the last few decades and varies between 10-40% depending on geographical location, with up to 25% of Canadians being affected. It is defined as an IgE-mediated inflammatory process affecting the nasal mucosa in a previously sensitised individual.2 When an atopic patient is exposed to an allergen, the patient develops specific IgE antibodies which become bound to mast cells. Re-exposure to this allergen results in two distinct phases of inflammation: an early phase occurring within minutes, due to mast cell degranulation which causes nasal itching, congestion and discharge; and a late phase occurring after several hours, due to eosinophil activation resulting in increased mucous production, nasal blockage and hyposmia.